PIMECROLIMUS CREAM IN CLINICAL PRACTICE OF CHILDREN'S ALLERGOLOGIST IMMUNOLOGIST - L.M. Ogorodova; I.A. Deev; F.I. Petrovsky; V.A. Revyakina; S.V. Bychkovskaya; T.G. Golosova; N.V. Kazakevich; D.S. Korostovtsev; V.R. Lipina; I.V. Sidorenko; N.A. Smirnov; B.A. Chernyak (Педиатрическая фармакология)
The object of the investigation was to estimate the basic therapy of atopic dermatitis (ad) in children and to analyze pimecrolimus application in clinical practice of children's allergologists immunologist. A multi centered retrospective study analysis involving 360 children aged 0–17 with atopic dermatitis of different severity was carried out. Insufficient effectiveness of implementation of main points of national program «atopic dermatitis and skin infections in children: diagnostics, treatment and prophylaxis» is determined. 37,4% cases of discrepancies in diagnoses by severity of atopic dermatitis in case of physician evaluation and on the scale of SCORAD, low level of control over blood pressure and high usage of systemic corticosteroids are registered. The application of pimecrolimus is revealed in 11,3% patients. It is essential to use more extensively the strategy of prolonged anti-inflammatory therapy of ad, including pimecrolimus use.Key words: atopic dermatitis, pharmacotherapy, pimecrolimus, children, treatment.